Kinetics and mechanism of Oxidation of Some Secondary Alcohols by N-Bromobenzamide - Poorey, Archana; Shaastry, L.V.; Seeriya, V.K.; Shaastry, V.R. (Asian Journal of Chemistry, 2010)
Kinetic studies in the oxidation of some secondary alcohols by N-bromobenzamide has been made in aqueous acetic acid in the presence of mercuric acetate. The reaction is first order with respect to the oxidant and near about one with respect to the substrates. The order with respect to perchloric acid varies with the change in perchloric acid concentration. The reaction is retarded by the initial addition of benzamide and is enhanced by the added potassium bromide. The activation parameters have been calculated and a suitable mechanism has been proposed.